Ernest Jones, Chartism, and the romance of politics 1819-1869 - Taylor, Miles (Oxford University Press, 2003)
In this biography of Ernest Jones (1819-69), the last of the Chartist leaders, the author interweaves an account of his literary achievement with his political career, revealing Jones as the mid-Victorian incarnation of Shelley's romantic vision of the poet as patriot.